Probability distribution functions of sup 12CO(J = 1 → 0) brightness and integrated intensity in M51: The PAWS view - Hughes, Annie; Meidt, Sharon E.; Schinnerer, Eva; Colombo, Dario; Pety, Jerôme; Dumas, Gaëlle; Schuster, Karl F.; Leroy, Adam K.; Dobbs, Clare L.; García-Burillo, Santiago; Thompson, Todd A.; Kramer, Carsten (The Astrophysical journal, 2013)
We analyze the distribution of CO brightness temperature and integrated intensity in M51 at ∼40 pc resolution using new sup 12CO(J = 1 → 0) data from the Plateau de Bure Arcsecond Whirlpool Survey (PAWS). We present probability distribution functions (PDFs) of the CO emission within the PAWS field of view, which covers the inner ∼11 × 7 kpc of M51. We find clear variations in the shape of CO PDFs both within different M51 environments, defined according to dynamical criteria, and among M51 and two nearby low-mass galaxies, M33 and the Large Magellanic Cloud (LMC). Globally, the PDFs for the inner disk of M51 can be represented by narrow lognormal functions that cover ∼1-2 orders of magnitude in CO brightness and integrated intensity. The PDFs for M33 and the LMC are narrower and peak at lower CO intensities, consistent with their lower gas surface densities. However, the CO PDFs for different dynamical environments within the PAWS field depart significantly from the shape of the global distribution. The PDFs for the interarm region are approximately lognormal, but in the spiral arms and central region of M51, they exhibit diverse shapes with a significant excess of bright CO emission. The observed environmental dependence on the shape of the CO PDFs is qualitatively consistent with changes that would be expected if molecular gas in the spiral arms is characterized by a larger range of average densities, gas temperatures, and velocity fluctuations, although further work is required to disentangle the relative importance of large-scale dynamical effects versus star formation feedback in regulating these properties. We show that the shape of the CO PDFs for different M51 environments is only weakly related to global properties of the CO emission, e.g., the total CO luminosity, but is strongly correlated with properties of the local giant molecular cloud (GMC) and young stellar cluster populations, including the shape of their mass distributions. For galaxies with strong spiral structure such as M51, our results indicate that galactic-scale dynamical processes play a significant role in the formation and evolution of GMCs and stellar clusters.